IDENTIFYING TYPES OF AFFIXES IN ENGLISH AND BAHASA INDONESIA - Serly Natalia; Tita Wulandari (Politeknik Negeri Sriwijaya, 2017)
The objectives of this study are to identify types of affixes which are applied in English and Bahasa Indonesia. The objects of this study were affixes which are applied both in English and Bahasa Indonesia in forming new words.The researcher used Lieber’s theory (2009) to explain types of English affixes and used Alwi, . The researcher also explained types of Bahasa Indonesia affixes based on Alwi, Dardjowidjojo, Lapoliwa, and Moeliono’s theory (2003). It was a library research study, therefore, this study used documentation technique as data collection instrument. The findings showed that (1) English has six types of affixes out of seven types from Lieber. They are prefixes, suffixes, infixes, circumfixes, interfixes, and simulfixes, (2) Bahasa Indonesia has four types of affixes. They are prefixes, suffixes, infixes, and circumfixes. (3) there are four similarities type of affixes that had by English and Bahasa Indonesia affixes, both of them have prefixes, suffixes, infixes and circumfixes. (4) English does not own transfixes. Lastly, (5) Bahasa Indonesia does not own interfixes, simulfixes and transfixes.